Consumers' Preferences for "Bicycle Poultry" in Benin: Implications for the Design of Breeding Schemes - Epiphane Sodjinou; Arne Henningsen; Delphin O. Koudande; Gauthier Biaou; Guy Apollinaire Mensah (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2014)
Village poultry, also termed "bicycle poultry," is produced in scavenging farming systems and is a chewy meat with a low fat content, and constitutes an important source of meat in many African countries. This study investigates consumers' preferences regarding the physical traits of these birds (notably chickens, ducks and guinea fowl) in the Republic of Benin. For this purpose, we applied the hedonic price method on field data collected from retailers in four urban and five rural markets. We found that meatier drake and meatier guinea fowl with white plumage are preferred by consumers who are willing to pay a premium for these types of birds. The factors which significantly influence the price of chicken are the breed of the bird, the plumage color, the meatiness and the age of the bird. Consumers are willing to pay a price premium for meatier birds of traditional breeds with white plumage color and aged between six and twelve months. Thus, efforts to improve local breeds should stress these preferred traits.
Keywords: D12; Q13; Q11; 330; Village poultry; consumer preferences; willingness to pay; breeding traits; the Republic of Benin